Asymmetric Electrophilic Difluoromethylthiolation of Indanone-Based β-Keto Esters Using Difluoromethanesulfonyl Hypervalent Iodonium Ylides - Gondo, Satoshi; Matsubara, Okiya; Chachignon, Hélène; Sumii, Yuji; Cahard, Dominique; Shibata, Norio (Molecules (Basel, Switzerland), 2019)
The first electrophilic diastereoselective direct introduction of the difluoromethylthio group is described. We used a chiral auxiliary-based approach to illustrate the versatility of our recently developed difluoromethanesulfonyl hypervalent iodonium ylide reagents for the difluoromethylthiolation of indanone-based β-keto esters. Chiral SCF2H-featuring compounds were obtained in up to 93% ee value.